The complete chloroplast genome of Aster scaber Thunb. 1784 (Asteraceae) - Yue Sheng; Yu-tong Huang; Yan-ping Xing; Chun-yan Li; Zi-xin Tang; Yan-yun Yang; Liang Xu (Mitochondrial DNA. Part B. Resources)
Aster scaber Thunb. (1784) is primarily distributed in eastern Asia,  has a total length of 152,778 bp and consists of a large single copy (LSC) region of 84,517 bp, a small single copy (SSC) region of 18,277 bp, and two inverted repeat (IRs) regions of 24,992 bp . The GC content is 37.31%. A total of 133 genes were annotated, including 88 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. Phylogenetic analysis using the maximum likelihood method showed that A. scaber is closely related to Aster species. This study provides chloroplast genome resource for further research on the phylogenetics and resource development of A. scaber.